The Ataköy vertical array (Turkey): Insights into seismic wave propagation in the shallow-most crustal layers by waveform deconvolution - Parolai, Stefano; Ansal, Atilla; Kurtulus, Asli; Strollo, Angelo; Wang, Rongjiang; Zschau, J. (Geophysical journal international, 2009)
A vertical array of accelerometers was installed in Ataköy (western Istanbul) with the long-term aim of improving our understanding of in situ soil behaviour, to assess the modelling and parametric uncertainties associated with the employed methodologies for strong-motion site-response analysis, and for shallow geological investigations. Geotechnical and geophysical investigations were carried out to define the subsoil structure at the selected site. Data associated with 10 earthquakes (2.7 < M < 4.3) collected during the first months of operation of the array were used to image the upgoing and downgoing waves by deconvolution of waveforms recorded at different depths. Results have shown that the velocity of propagation of the imaged upgoing and downgoing waves in the borehole is consistent with that of S or P waves, depending on the component of ground acceleration analysed but independent of the chosen signal window. In particular, an excellent agreement was found between the observed upgoing and downgoing wave traveltimes and the ones calculated using a model derived by seismic noise analysis of array data. The presence of a smaller pulse on the waveforms obtained by deconvolution of the horizontal components suggests both internal S-wave reflection and S-to-P mode conversion, as well as a not normal incidence of the wavefield. The presence of a pulse propagating with S-wave velocity in the uppermost 25 m in the waveforms obtained by the deconvolution of the vertical components suggests P-to-S mode conversion. These evidences imply that, even when site amplification is mainly related to 1-D effects, the standard practice in engineering seismology of deconvolving the surface recording down to the bedrock using an approximate S-wave transfer function (generally valid for vertical incidence of SH waves) might lead to errors in the estimation of the input ground motion required in engineering calculations. Finally, downgoing waves with significant amplitudes were found down to 70 m and even to 140 m depth. This result provides a warning about the use of shallow borehole recordings as input for the numerical simulation of ground motion and for the derivation of ground motion prediction relationships.